2022
DOI: 10.1002/ptr.7493
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of gypenoside XVII against ischemia/reperfusion injury: Role of endoplasmic reticulum stress, autophagy, and mitochondrial fusion fission balance

Abstract: Gypenoside XVII (GP‐17), a tetracyclic triterpene saponin isolated from the functional food Gynostemma pentaphyllum, has been demonstrated protective effects against cerebrovascular and cardiovascular diseases on multiple disease models. In this study, we established a myocardial infarction (MI) model by ligating the left anterior descending coronary artery, and explored whether GP‐17 prevent myocardial ischemia/reperfusion (I/R) injuries in mice. Compared with the I/R group, GP‐17 significantly improved the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Many of these drugs and therapies have been tested today and have proven superior efficacy ( 33 ). Recently, some studies found that saponins from TCM can protect against myocardial ischemia-reperfusion injury through various mechanisms ( 4 , 34 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these drugs and therapies have been tested today and have proven superior efficacy ( 33 ). Recently, some studies found that saponins from TCM can protect against myocardial ischemia-reperfusion injury through various mechanisms ( 4 , 34 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Five articles did not report infarct size as mentioned in the inclusion criteria, three lacked a placebo group, and three used saponin conversion products as an intervention. Finally, 17 studies of 386 animals (254 in the saponin treatment group and 132 in the control group) met the predetermined inclusion criteria and were eventually included in our meta-analysis (Figure 1) (4,5,10,13,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Table 1 shows comprehensive information for each study.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…So arjunolic acid and Gyp-17 have a role as a metabolite and an antioxidant. [88,103,104] 3.6. Alkaloids 3.6.1.…”
Section: Gypenoside XVII Gypenoside Xvii (Gyp-17mentioning
confidence: 99%
“…Gypenoside XVII (GP-17; molecular formula: C 48 H 82 O 18 ; molecular weight: 947.2 g/mol; Figure 1A) is a gypenoside monomer found in medicinal plants such as Gynostemma pentaphyllum or Panax notoginseng. Several experimental studies have reported various pharmacological properties to GP-17, including immunoregulatory, anti-inflammatory, neuroprotective, cardioprotective, lipid-lowering, and neuroprotective effects [11][12][13][14][15][16]. Regarding its neuroprotective effect, GP-17 attenuated cerebral infarct volume and alleviated neurological dysfunction in a middle cerebral artery occlusion/reperfusion (MCAO/R) rat model [17].…”
Section: Introductionmentioning
confidence: 99%